The Effect of a Combination of Rubber Wood and Palm Shells as a Source of Fuel in the Fumigation Process Ribbed Smoked Sheet (RSS) - Mulia, Sukri; Yurizki, Yusra; Nasution, Nurhadida (Journal of Agriculture, 2023)
Natural rubber is one of the ingredients result that there are many rubber plantation in Indonesia, products of natural rubber product manufactured by company nationwide Rubber Company is lateks dark, ribbed smoked sheet and crumb rubber one of products manufactured by the factory rubber factory in Indonesia is ribbed smoked sheet. ribbed smoked sheet is one kind of processed products derived from latex or latex have a brisiliensis rubber plants are processed in mechanical and chemical engineering using a drying room with smoke, almost all factories do fumigation only using rubber wood as fuel, the researchers are looking for alternative fuel using palm shells are pretty much and easily accessible in the palm oil mill.  The purpose of this study was to determine the effects of fuel combination of rubber wood and palm shells as a fuel source fumigation ribbed smoked sheet this study uses fuel of rubber wood and palm shells by using a laboratory scale fumigation, the first combination used 100% rubber woods, the second combination used 50% rubber woods and 50% palm shells the third combination used 100% palm shells. Ribbed smoked sheet  which is observed  according  to the ribbed smoked sheet  Indonesian national standard (SNI) the result of the study indicated that wood rubber fuel produce the best ribbed smoked sheet than palm shells and the combination of palm shells and rubber wood.